Inconsistent Condom Use among Iranian Male Drug Injectors - Narenjiha, Hooman; Rafiey, Hassan; Ahmadi, Khodabakhsh; Assari, Shervin; Tavakoli, Mahmood; Jafari, Firoozeh; Yarmohamadivasel, Mosaieb (Frontiers in Psychiatry, 2014)
Objectives: The aim of this study was to determine the prevalence and associated factors of inconsistent condom use among Iranian male injection drug users (IDUs). Materials and methods: Data came from the national Iranian behavioral survey of drug dependence, which sampled 7,743 individuals with drug dependence, from medical centers, prisons and streets in 29 provinces in Iran, 2007. This study included all individuals who were male, IDUs, and were sexually active (n = 1,131). The main outcome was inconsistent condom use which was assessed using a single item. A logistic regression was used to determine the association between socio-economic data, drug use data, and high risk injection behaviors with inconsistent condom use. Result: 83.3% of sexually active IDUs (n=965) reported inconsistent condom use. Based on the logistic regression, likelihood of inconsistent condom use was higher among those with a history of syringe sharing (Odds Ratio [OR]; 1.63, 95% Confidence Interval CI; 1.13- 2.34), but lower among those with higher education levels (OR; 0.34, 95% CI; 0.14- 0.82), those who mostly inject at home (OR; 0.09, 95% CI; 0.02- 0.47) and those with a history of treatment (OR; 0.54, 95% CI; 0.31- 0.94). Conclusion: Because of the link between unsafe sex and risky injecting behaviors among Iranian IDUs, combined programs targeting both sexual and injection behavior may be more appropriate than the programs which target sexual or injection behavior. The efficacy of combined programs should be, however, compared with traditional programs that only target sexual or injection behavior of IDUs.